2022
DOI: 10.1155/2022/4224701
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Contrast‐Enhanced Spectral Mammography and Contrast‐Enhanced MRI in Screening Multifocal and Multicentric Lesions in Breast Cancer Patients

Abstract: Objectives. We aimed to determine the difference between contrast-enhanced spectral mammography (CESM) and contrast-enhanced magnetic resonance imaging (CE-MRI) in detecting multifocal and multicentric breast cancer (MMBC). Methods: This study was conducted among breast cancer patients between July 1, 2017, and May 30, 2021. The sensitivity, specificity, and accuracy of CESM and CE-MRI in the diagnosis of MMBC were evaluated with pathological results as the gold standard. Results. A total of 188 lesions were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…In a further retrospective study of a highly selected group of 54 women already known to have multifocal or multicentric breast cancer [ 22 ], 188 lesions were found, of which 177 were cancers. No distinction was made between index and additional lesions and details regarding the method of imaging-pathology correlation were not described.…”
Section: Resultsmentioning
confidence: 99%
“…In a further retrospective study of a highly selected group of 54 women already known to have multifocal or multicentric breast cancer [ 22 ], 188 lesions were found, of which 177 were cancers. No distinction was made between index and additional lesions and details regarding the method of imaging-pathology correlation were not described.…”
Section: Resultsmentioning
confidence: 99%
“…Feng et al (11) and Steinhof-Radwan ́ska et al ( 12) also confirmed that the specificity of CEM was higher than that of MRI, at 36.4% vs. 63.6% and 96.15% vs. 92.31%, respectively. By contrast, Moustafa et al (3) reported that CEM showed high sensitivity in multiple lesion detection, reaching 100%, but with a suboptimal specificity of approximately 97.3% because some benign lesions could show significant enhancement, such as in inflammatory lesions and intra-ductal papillomas.…”
Section: Discussionmentioning
confidence: 83%
“…It showed a good accuracy in multifocality and multicentricity assessment (9,10). The advantages of MRI include its ability to image the chest wall and axilla and the lack of ionizing radiation and breast compression (11). However, its limitations include its high cost, lengthy procedure, not being feasible in patients with claustrophobia and non-MR compatible cardiac devices, and a high rate of false-positive results, which may lead to more aggressive treatment plans than required, consequently affecting the patient's quality of life (12,13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, examining the real impact of the most recent advancements in standard imaging techniques on breast cancer prevention, such as digital breast tomosynthesis (DBT) and automated breast ultrasound (ABUS), could be incredibly challenging, especially in women with dense breasts. In addition, contrast-enhanced spectral mammography (CESM) could be considered a true alternative to the most expensive magnetic resonance imaging (MRI) [ 10 , 11 ]. On the other hand, the evaluation of fast MRI could have a great impact on breast cancer prevention, especially in women at high risk [ 12 ].…”
mentioning
confidence: 99%